Effect of calcium supplementation on mucosal cell proliferation in high risk patients for colon cancer. Issue 3 (March 1989) - Gregoire, R C; Stern, H S; Yeung, K S; Stadler, J; Langley, S; Furrer, R; Bruce, W R
Abstract : Recent findings suggest that supplemental calcium could lower the abnormally high proliferation rate found in the colonic mucosa of subjects at high risk for colon cancer. In this double blind controlled study, this effect in volunteers previously operated upon for a colorectal adenocarcinoma was tested. Thirty subjects were randomised to receive either elemental calcium 1200 mg/day or a placebo. Mucosal proliferation was measured with tritiated thymidine labelling before and after the 30 day intervention period. Diets, faecal pH and the concentration of calcium and bile acids in the aqueous phase of feaces were also measured. Labelling index did not differ significantly in the two groups before intervention (placebo 4.0(2.4) v calcium 4.9(2.9), but the difference approached significance afterwards (4.4(2.4) v 6.5(3.4), p = 0.06). Individual changes occurring with intervention were tabulated and comparison of the means for the groups was not significant (delta = 0.3 vs delta = 1.8, p = 0.11). Calcium concentration, faecal pH and deoxycholic acid concentration increased in the calcium group (p = 0.02, 0.005 and 0.004 respectively). Calcium does not show any effect in decreasing colonic mucosal proliferation in this high risk group for colon cancer; it may increase faecal pH and the production of deoxycholic acid in the colon.